2014
DOI: 10.1016/j.ab.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Generating NMR chemical shift assignments of intrinsically disordered proteins using carbon-detected NMR methods

Abstract: There is an extraordinary need to describe the structures of intrinsically disordered proteins (IDPs) due to their role in various biological processes involved in signaling and transcription. However, general study of IDPs by NMR spectroscopy is limited by the poor 1H-amide chemical shift dispersion typically observed in their spectra. Recently, 13C direct-detected NMR spectroscopy has been recognized as enabling broad structural study of IDPs. Most notably, multi-dimensional experiments based on the 15N,13C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 47 publications
(63 reference statements)
4
48
0
Order By: Relevance
“…We were not able to resolve this ambiguity using carbon detection experiments due to the lack of sufficiently concentrated samples for these relatively insensitive experiments. 36 Neighbor corrected chemical shift predictions 8 indicated that the C-terminal tails have a slight propensity for β -sheet formation (Figure S2). This result is in contrast to computer simulations showing a bias of the C-terminal tails of human tubulin isoforms toward α -helical conformations when simulated in isolation.…”
Section: Resultsmentioning
confidence: 99%
“…We were not able to resolve this ambiguity using carbon detection experiments due to the lack of sufficiently concentrated samples for these relatively insensitive experiments. 36 Neighbor corrected chemical shift predictions 8 indicated that the C-terminal tails have a slight propensity for β -sheet formation (Figure S2). This result is in contrast to computer simulations showing a bias of the C-terminal tails of human tubulin isoforms toward α -helical conformations when simulated in isolation.…”
Section: Resultsmentioning
confidence: 99%
“…All pulsed field gradients used in the experiments were applied for 1 ms with a sine shape. In all pulse sequences, unless otherwise noted by Sahu et al (25), the 90 band-selective 13 C pulses have the Q5 shape (or time reversed, Q5tr), and the band-selective 13 C 180 pulses use the Q3 shape with durations of 384 and 307 s, respectively. The standard 1 H, 15 N HSQC, C_CON, HNCO, and HNCACO experiments were used from the TopSpin pulse program library.…”
Section: Expression and Purification Of His-c-src-sh3mentioning
confidence: 99%
“…Briefly, several of the proline resonances were uniquely assigned by their presence in the Ala-specific CON, Ser-specific CON, and TAVI-specific CON spectra. Additional resonance assignments were generated from (H Nflip)N(CA)CON and (H N -flip)N(CA)NCO spectra (25). All NMR data were processed in TopSpin version 2.1 and converted to Sparky (26) format for data analysis.…”
Section: Expression and Purification Of His-c-src-sh3mentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, 80 mM imidazole pH 6.5, 50 mM KCl, 10% glycerol, 2 mM DTT and 10% D 2 NMR Spectra were collected at the Lloyd Jackman NMR facility at the Pennsylvania State University on Bruker Avance-III spectrometers operating at proton frequencies of 500, 600 or 850 MHz equipped with TCI single-axis gradient cryoprobes ( 1 H/ 13 C/ 15 N/ 2 H) with enhanced sensitivity for 1 H and 13 C. Phosphorous-detect experiments were performed on a 500 MHz Bruker Avance-III-HD spectrometer equipped with a broadband (BBO) Prodigy CryoProbe. Chemical shift assignments were made using 13 C-Direct Detect methods developed in-house 17,41,42 , as well as standard 1 H-Detect triple resonance experiments. 13 C and 31 P chemical shifts were referenced to 4,4-dimethyl-4-silapentane-1-sulfonic acid (DSS) and phosphoric acid standards, respectively.…”
Section: Methodsmentioning
confidence: 99%